Bank Ownership : Trends and Implications - Cull, Robert; Martinez Peria, Maria Soledad; Verrier, Jeanne (World Bank, Washington, DC, 2018)
This paper presents recent trends in government and foreign bank ownership across countries and summarizes the evidence regarding the implications of bank ownership structure for bank performance and competition, financial stability, and access to finance. The evidence reviewed suggests that foreign-owned banks tend to be more efficient than domestic banks in developing countries, promote competition in host banking sectors, and help stabilize credit when host countries face idiosyncratic shocks. But there are trade-offs, since foreign-owned banks can also transmit external shocks and might not always contribute to expanding access to credit. The record on the impact of government bank ownership suggests few benefits, especially for developing countries.